PENGARUH FORMULASI UNSUR HARA MIKRO DAN N TERHADAP KANDUNGAN HARA DALAM JARINGAN TANAMAN DAN HASIL KEDELAI PADA TANAH GAMBUT (Effect of formulation micro nutrients and n of nutrient content in tissue plant and soybean yield on peat soil) - tiyah, Sus; Zubaidah, Siti (Universitas Palangka Raya, 2008)
ABATRACTThe main objective of this study is the found of four level micro nutrients (Fe, Zn, Mn, Cu)dan N on peat soil to reach for enough level in tissue plant soybean so optimal soybean yield. Thestudy was carried out in Kalampangan Vilage, Sabangau Palangka Raya from June until September2005. The treatments aplied in this study were: fo = 5 ton manure fertilizer ha-1+3 ton dolomit ha-1 +1,2t ha-1 dust vegetation on peat; f1 = fo + (30 kg Fe+20 kg Zn+15 kg Mn+15kg Cu) ha-1 + 100 kg Ureaha-1; f2 = fo + (30 kg Fe+20 kg Zn+15 kg Mn+15kg Cu) ha-1 + 150 kg Urea ha-1; f3 = fo + (30 kgFe+20 kg Zn+15 kg Mn+15kg Cu) ha-1 + 200 kg Urea ha-1; f4 = fo + (35 kg Fe+25 kg Zn+20 kgMn+20 kg Cu) ha-1 + 100 kg Urea ha-1; f5 = fo + (35 kg Fe+25 kg Zn+20 kg Mn+20 kg Cu) ha-1 + 150kg Urea ha-1; f6 = fo + (35 kg Fe+25 kg Zn+20 kg Mn+20 kg Cu) ha-1 + 200 kg Urea ha-1; f7 = fo +(40 kg Fe+30 kg Zn+25 kg Mn+25 kg Cu) ha-1 + 100 kg Urea ha-1; f8 = fo + (40 kg Fe+30 kg Zn+25kg Mn+25 kg Cu) ha-1 + 150 kg Urea ha-1; f9 = fo + (40 kg Fe+30 kg Zn+25 kg Mn+25 kg Cu) ha-1 +200 kg Urea ha-1, the combination with two varietas namely are Sibayak and Wilis (symbol v; Sibayak= v1 dan Wilis = v2). The result showed that nutrient content on tissue plant soybean verietas Sibayakand Wilis increased together with increasing four level micro nutrients (Fe, Zn, Mn, Cu) and N. Thetreatments f7, f8 and f9 are of the ttreatment can increassed mikro and makro nutrient in tissue plantsoybean to enough category except P and K nutrients. Amelioration of peat soil with some level fourlevel micro nutrients (Fe, Zn, Mn, Cu) on the formulation with some level N, have effects verysignificant of increased the soybean verieteas Sibayak and Wilis yield. Treatment F8 give the bestyield of seed per square (340,92 g).Keywords: formulation micro nutrients and N, peat soil, nutrient in tissue plant soybean, soybeanyield